Trademark Squatting: A Fraudulent Strategy in Trademark Claims - Yoyo Arifardhani; Maimun (Inovasi Pratama Internasional. Ltd, 2026)
Trademark squatting is a legal phenomenon that is increasingly prevalent in line with the development of the global business world, where certain parties register unregistered trademarks belonging to others with the aim of obtaining illegitimate profits. This study aims to examine and analyze the concept of trademark squatting in the Indonesian trademark legal system, identify regulatory weaknesses that allow this practice to occur, and formulate ideal legal protection measures for brand owners who become victims. The research method used is normative juridical with a statute approach, a conceptual approach, and a case approach. The results show that trademark squatting in Indonesia is facilitated by loopholes in the first-to-file registration system adopted by Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Although there are protection mechanisms through the concepts of bad faith and well-known trademarks, their implementation in the field still faces various obstacles. Reconstruction of the trademark registration system based on actual use and strengthening substantive examinations by the Directorate General of Intellectual Property are key to preventing trademark squatting in the future.